UV (ultraviolet) curing insulating tape for cylindrical battery water-cooling plate as well as preparation method, use method and application of UV curing insulating tape

By using UV-curable insulating tape including insulating substrate, UV-curable acrylic pressure-sensitive adhesive and release film on the water-cooled plate of automotive cylindrical battery, the problems of poor uniformity and high production cost of existing insulating paints are solved, and the problem of Efficient insulation protection and cooling effect.

CN119144242APending Publication Date: 2024-12-17CYBRID TECHNOLOGIES INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411269134.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

In the prior art, the water-cooled plate cooling system of automotive cylindrical batteries requires insulating materials, but the existing insulating paint has poor uniformity, high production costs and easy to contaminate, and the spraying equipment has a large investment and high energy consumption, making it difficult to meet the needs of new energy vehicles. High performance and safety requirements for battery pack cooling.

Method used

UV cured insulating tape including insulating substrate, UV-curable acrylic pressure-sensitive adhesive and release film are used. UV curing is improved after normal temperature bonding, and the structural strength and insulation consistency are improved, which is suitable for insulating protection of water-cooled plates of cylindrical batteries.

Benefits of technology

It realizes efficient insulation protection, has excellent bending resistance, high bonding strength, high working efficiency and good insulation consistency, which reduces production costs and equipment investment and improves the cooling effect of the battery pack.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144242A_ABST
    Figure CN119144242A_ABST
Patent Text Reader

Abstract

The invention provides a UV curing insulating tape for a water cooling plate of a cylindrical battery as well as a preparation method and application of the UV curing insulating tape. The UV curing insulating tape comprises an insulating base material, a UV-curable acrylic pressure-sensitive adhesive and a release film which are arranged in sequence, the UV curing insulating tape has a pressure-sensitive characteristic in the initial stage, can be attached to the surface of a cylindrical battery water-cooling plate by applying pressure at normal temperature, can achieve higher structural strength after being attached and fixed and being subjected to UV curing, also has excellent bending resistance and excellent bonding performance, and can be applied to the surface of the cylindrical battery water-cooling plate. The water-cooling plate insulation protection device is suitable for insulation protection of the water-cooling plate for the cylindrical battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of adhesive tapes, and in particular relates to a UV-curing insulating adhesive tape for a cylindrical battery water-cooling plate, and a preparation method, a use method and an application thereof. Background Art

[0002] In recent years, with the continuous development of new energy vehicles, higher and higher requirements have been put forward for the performance and safety of new energy vehicles. As the heart of new energy vehicles, the battery pack provides power for the entire vehicle. During the charging and discharging process, the battery will release a lot of heat, causing the temperature inside the battery pack to rise, so the battery pack needs to be cooled.

[0003] At present, cooling and heating of cylindrical batteries for vehicles are the mainstream. The water-cooling plate will be assembled close to the battery for cooling, and then the water-cooling plate needs to be bent according to the shape of the battery, but there needs to be material between the water-cooling plate and the battery for insulation. The electrical insulation between the battery and the water-cooling plate usually requires spraying a layer of insulating paint on the serpentine water-cooling plate. However, the equipment investment required for spraying insulating paint is large, the energy consumption is high, and it is easy to produce pinholes resulting in poor insulation. The material and processing costs are high. At the same time, the uniformity of existing insulating paint is poor, the production yield is low, and it is easy to cause pollution.

[0004] Therefore, in response to the above problems, it is necessary to develop a UV-curable insulating tape for cylindrical battery water cooling plates with excellent bending resistance, high bonding strength and good insulation consistency. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a UV-curing insulating tape for a cylindrical battery water-cooling plate and a preparation method, a use method and an application thereof. The UV-curing insulating tape can be bonded at room temperature and can achieve higher structural strength after UV curing. At the same time, it has the advantages of excellent bending resistance, high bonding strength, high working efficiency and good insulation consistency, and is suitable for insulation protection of cylindrical battery water-cooling plates.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a UV-curable insulating tape for a cylindrical battery water-cooling plate, wherein the UV-curable insulating tape comprises an insulating substrate, a UV-curable acrylic pressure-sensitive adhesive, and a release film which are arranged in sequence.

[0008] The UV-curable insulating tape provided by the present invention comprises an insulating substrate, a UV-curable acrylic pressure-sensitive adhesive and a release film which are arranged in sequence. The UV-curable insulating tape has the characteristics of a pressure-sensitive tape in the initial stage, and can be adhered to the surface of a cylindrical battery water-cooling plate by applying pressure at room temperature. After being adhered and fixed and then UV-cured, a higher structural strength can be achieved. At the same time, it has the advantages of excellent bending resistance, high bonding strength, high working efficiency and good insulation consistency, and is suitable for insulation protection of cylindrical battery water-cooling plates.

[0009] Preferably, the thickness of the insulating substrate is 10 to 200 μm, for example, 10 μm, 20 μm, 40 μm, 60 μm, 80 μm, 100 μm, 120 μm, 140 μm, 160 μm, 180 μm or 200 μm, and more preferably 50 to 100 μm.

[0010] Preferably, the material of the insulating substrate includes any one or a combination of at least two of polyethylene terephthalate (PET), polyvinyl chloride (PVC), thermoplastic polyolefin (TPO), thermoplastic polyurethane elastomer (TPU), polyamide (PA), polyethylene (PE) or polypropylene (PP).

[0011] Preferably, the thickness of the UV-curable acrylic pressure-sensitive adhesive is 20-100 μm, for example, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm.

[0012] Preferably, the raw material for preparing the UV-curable acrylic pressure-sensitive adhesive is UV-curable acrylic adhesive solution.

[0013] Preferably, the UV-curable acrylic adhesive comprises the following components in parts by weight:

[0014] 10 to 90 parts by weight of acrylic acid ester polymer;

[0015] 10 to 90 parts by weight of epoxy resin;

[0016] 0.5 to 5 parts by weight of photoinitiator.

[0017] The content of the acrylic acid ester polymer may be 10 parts by weight, 20 parts by weight, 30 parts by weight, 40 parts by weight, 50 parts by weight, 60 parts by weight, 70 parts by weight, 80 parts by weight or 90 parts by weight.

[0018] The epoxy resin may be used in an amount of 10 parts by weight, 20 parts by weight, 30 parts by weight, 40 parts by weight, 50 parts by weight, 60 parts by weight, 70 parts by weight, 80 parts by weight or 90 parts by weight.

[0019] The amount of the photoinitiator can be 0.5 parts by weight, 1 part by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight, 4 parts by weight or 4.5 parts by weight, etc.

[0020] Preferably, the acrylate polymer is prepared by free radical polymerization of structural monomers and optionally functional monomers.

[0021] Preferably, the structural monomer includes any one of methyl acrylate, methyl methacrylate, butyl acrylate, isooctyl acrylate, isobornyl acrylate or isobornyl methacrylate, or a combination of at least two thereof.

[0022] Preferably, the functional monomer includes a combination of at least two of acrylic acid, methacrylic acid, glycidyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, acrylamide, N-vinyl caprolactam or N-vinyl pyrrolidone.

[0023] Preferably, the epoxy resin includes any one of bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol F epoxy resin, bisphenol S epoxy resin, hydrogenated bisphenol S epoxy resin, novolac epoxy resin, hydrogenated novolac epoxy resin, biphenyl epoxy resin, hydrogenated biphenyl epoxy resin, phenol epoxy resin, hydrogenated phenol epoxy resin, distyrene epoxy resin, polyurethane modified epoxy resin, polyether modified epoxy resin, rubber modified epoxy resin, silicone modified epoxy resin, dimer acid modified epoxy resin or aliphatic epoxy resin, or a combination of at least two thereof.

[0024] Preferably, the photoinitiator includes any one of diazonium salts, diaryliodonium salts, triarylsulfonium salts, alkylsulfonium salts, iron arene salts or sulfonyloxy ketones, or a combination of at least two thereof.

[0025] Preferably, the UV-curable acrylic adhesive further comprises any one of a tackifying resin, a flame retardant or a filler, or a combination of at least two thereof.

[0026] Preferably, the content of tackifying resin in the UV-curable acrylic adhesive is ≤10 parts by weight, for example, 10 parts by weight, 9 parts by weight, 8 parts by weight, 7 parts by weight, 6 parts by weight, 5 parts by weight, 4 parts by weight, 3 parts by weight, 2 parts by weight or 1 part by weight.

[0027] Preferably, the tackifying resin includes any one of aromatic resin, rosin terpene phenol resin or modified rosin resin, or a combination of at least two of them.

[0028] Preferably, the content of the flame retardant in the UV-curable acrylic adhesive is ≤30 parts by weight, for example, 30 parts by weight, 25 parts by weight, 20 parts by weight, 15 parts by weight, 10 parts by weight or 5 parts by weight.

[0029] Preferably, the flame retardant includes any one or a combination of at least two of a phosphorus-based flame retardant, a nitrogen-based flame retardant, a silicon-based flame retardant, a metal hydroxide flame retardant, a metal oxide flame retardant, a flame-retardant acrylic resin or a metal boride flame retardant.

[0030] Preferably, the content of filler in the UV-curable acrylic adhesive is ≤5 parts by weight, for example, 5 parts by weight, 4 parts by weight, 3 parts by weight, 2 parts by weight or 1 part by weight.

[0031] Preferably, the filler comprises fumed silica.

[0032] Preferably, the fumed silica includes any one of AEROSIL 150, AEROSIL 200 or AEROSIL 380, or a combination of at least two of them.

[0033] Preferably, the UV light-curable acrylic adhesive is obtained by mixing an acrylic ester polymer, an epoxy resin, a photoinitiator, optionally a tackifying resin, optionally a flame retardant and optionally a filler.

[0034] Preferably, the release film has a thickness of 25 to 100 μm, for example, 25 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm, and more preferably 25 to 50 μm.

[0035] Preferably, the release film comprises a transparent PET release film.

[0036] In a second aspect, the present invention provides a method for preparing the UV-curable insulating tape as described in the first aspect, the preparation method comprising: coating a UV-curable acrylic adhesive on an insulating substrate, and attaching a release film after drying to obtain the UV-curable insulating tape.

[0037] In a third aspect, the present invention provides a method for using the UV-curing insulating tape as described in the first aspect, the method comprising: sticking the UV-curing insulating tape to the surface of a cylindrical battery water-cooling plate, and completing the use of the UV-curing insulating tape through UV curing and standing.

[0038] Preferably, the energy density of the UV curing is 1000-5000 mJ / cm 2 , for example 1000mJ / cm 2 、1500mJ / cm 2 、2000mJ / cm2 、2500mJ / cm 2 、3000mJ / cm 2 、3500mJ / cm 2 、4000mJ / cm 2 、4500mJ / cm 2 or 5000mJ / cm 2 wait.

[0039] Preferably, the UV curing time is 1s to 5h, for example, 1s, 5s, 10s, 60s, 5min, 10min, 60min, 2h, 3h, 4h or 5h.

[0040] Preferably, the standing temperature is room temperature.

[0041] Preferably, the standing time is 1 to 100 h, for example, 1 h, 5 h, 10 h, 20 h, 30 h, 40 h, 50 h, 60 h, 70 h, 80 h, 90 h or 100 h.

[0042] In a fourth aspect, the present invention provides a use of the UV-curable insulating tape as described in the first aspect in the preparation of automotive cylindrical batteries.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] The UV-curable insulating tape for a cylindrical battery water-cooling plate provided by the present invention comprises an insulating substrate, a UV-curable acrylic pressure-sensitive adhesive and a release film which are arranged in sequence; the UV-curable insulating tape has a pressure-sensitive property in the initial stage, and can be attached to the surface of the cylindrical battery water-cooling plate by applying pressure at room temperature, and can achieve higher structural strength after being attached and fixed and UV-cured; at the same time, the UV-curable insulating tape also has the advantages of excellent bending resistance, excellent bonding performance, high working efficiency and good insulation consistency, and is suitable for insulation protection of cylindrical battery water-cooling plates. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 A schematic diagram of the cross-sectional structure of the UV-curable insulating tape provided by the present invention;

[0046] Among them, 1-insulating substrate, 2-UV curable acrylic pressure-sensitive adhesive, 3-release film. DETAILED DESCRIPTION

[0047] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0048] Unless otherwise specified, the raw materials involved in the following examples and comparative examples are conventional materials in the art and can be purchased commercially.

[0049] Preparation Example 1

[0050] A UV-curable acrylic adhesive solution comprises the following components in parts by weight:

[0051] 50 parts by weight of acrylate polymer;

[0052] Nan Ya bisphenol A epoxy resin NPEL-128E 50 parts by weight;

[0053] 2.5 parts by weight of iron aromatic salt IRGACURE 261;

[0054] 3 parts by weight of Arakawa Chemical rosin terpene phenol resin T-803L;

[0055] 5 parts by weight of Clariant organophosphorus flame retardant OP935;

[0056] 1 part by weight of fumed silica AEROSIL 150;

[0057] The preparation method of the acrylic ester polymer comprises: adding 70 parts by weight of butyl acrylate, 25 parts by weight of methyl acrylate, 5 parts by weight of glycidyl methacrylate, 50 parts by weight of ethyl acetate and 0.03 parts by weight of free radical initiator AIBN into a reactor, and polymerizing at 85° C. for 4 hours to obtain the acrylic ester polymer;

[0058] The preparation method of the UV-curable acrylic adhesive provided in this preparation example includes: mixing an acrylate polymer, Nan Ya bisphenol A epoxy resin NPEL-128E, iron aromatic salt IRGACURE 261, rosin terpene phenol resin, Clariant organophosphorus flame retardant OP935 and fumed silica AEROSIL 150 in a reactor for 1 hour to obtain the UV-curable acrylic adhesive.

[0059] Preparation Example 2

[0060] A UV-curable acrylic adhesive solution comprises the following components in parts by weight:

[0061]

[0062] The preparation method of the acrylic ester polymer comprises: adding 70 parts by weight of butyl acrylate, 25 parts by weight of methyl acrylate, 5 parts by weight of glycidyl methacrylate, 50 parts by weight of ethyl acetate and 0.03 parts by weight of free radical initiator AIBN into a reactor, and polymerizing at 85° C. for 4 hours to obtain the acrylic ester polymer;

[0063] The preparation method of the UV-curable acrylic adhesive provided in this preparation example includes: mixing an acrylate polymer, bisphenol A epoxy resin E51, iron aromatic salt IRGACURE 250, rosin terpene phenol resin, Clariant organophosphorus flame retardant OP935 and fumed silica AEROSIL 150 in a reactor for 1 hour to obtain the UV-curable acrylic adhesive.

[0064] Preparation Example 3

[0065] A UV-curable acrylic adhesive solution comprises the following components in parts by weight:

[0066]

[0067] 10 parts by weight of Clariant organophosphorus flame retardant OP935;

[0068] 1 part by weight of fumed silica AEROSIL 150;

[0069] The preparation method of the acrylic ester polymer and the preparation method of the UV-curable acrylic adhesive provided in this preparation example are the same as those in Preparation Example 1.

[0070] Preparation Example 4

[0071] A UV-curable acrylic adhesive solution, which differs from Preparation Example 1 only in that the amount of acrylate polymer used is 5 parts by weight, the amount of Nan Ya bisphenol A epoxy resin NPEL-128E used is 95 parts by weight, and other substances, amounts used and preparation methods are the same as those in Preparation Example 1.

[0072] Preparation Example 5

[0073] A UV-curable acrylic adhesive solution, which differs from Preparation Example 1 only in that the amount of acrylate polymer used is 95 parts by weight, the amount of Nan Ya bisphenol A epoxy resin NPEL-128E used is 5 parts by weight, and other substances, amounts used and preparation methods are the same as those in Preparation Example 1.

[0074] Comparative Preparation Example 1

[0075] An acrylic adhesive solution, which differs from Preparation Example 1 only in that Nan Ya bisphenol A epoxy resin NPEL-128E is not added, the amount of acrylic ester polymer used is 100 parts by weight, and other substances, amounts used and preparation methods are the same as those in Preparation Example 1.

[0076] Example 1

[0077] A UV curing insulating tape for a cylindrical battery water cooling plate, the cross-sectional structure diagram of which is shown in FIG. Figure 1As shown, it includes an insulating substrate 1, a UV-curable acrylic pressure-sensitive adhesive 2 and a release film 3 which are arranged in sequence;

[0078] The thickness of the insulating substrate 1 is 100 μm, and is specifically a PVC film;

[0079] The thickness of the UV-curable acrylic pressure-sensitive adhesive 2 is 30 μm, and the raw material for preparation is the UV-curable acrylic adhesive solution provided in Preparation Example 1;

[0080] The release film 3 has a thickness of 25 μm and is specifically a transparent PET film;

[0081] The preparation method of the UV-curable insulating tape provided in this embodiment comprises: applying the UV-curable acrylic adhesive provided in Preparation Example 1 on a PVC film by using a scraper, and then laminating a transparent PET film after drying in an oven to obtain the UV-curable insulating tape.

[0082] Example 2

[0083] A UV-curable insulating tape for a cylindrical battery water-cooling plate, the structure of which is the same as that of Example 1, comprising an insulating substrate, a UV-curable acrylic pressure-sensitive adhesive and a release film arranged in sequence;

[0084] The thickness of the insulating substrate is 50 μm, specifically a PET film;

[0085] The thickness of the UV-curable acrylic pressure-sensitive adhesive is 20 μm, and the raw material for preparation is the UV-curable acrylic adhesive solution provided in Preparation Example 2;

[0086] The thickness of the release film is 25 μm, specifically a transparent PET film;

[0087] The preparation method of the UV-curable insulating tape provided in this embodiment comprises: applying the UV-curable acrylic adhesive provided in Preparation Example 2 on a PET film using a scraper, and then laminating the film with a transparent PET film after drying in an oven to obtain the UV-curable insulating tape.

[0088] Example 3

[0089] A UV-curable insulating tape for a cylindrical battery water-cooling plate, the structure of which is the same as that of Example 1, comprising an insulating substrate, a UV-curable acrylic pressure-sensitive adhesive and a release film arranged in sequence;

[0090] The thickness of the insulating substrate is 80 μm, specifically a TPU film;

[0091] The thickness of the UV-curable acrylic pressure-sensitive adhesive is 100 μm, and the raw material for preparation is the UV-curable acrylic adhesive solution provided in Preparation Example 3;

[0092] The thickness of the release film is 50 μm, specifically a transparent PET film;

[0093] The preparation method of the UV-curable insulating tape provided in this embodiment comprises: applying the UV-curable acrylic adhesive provided in Preparation Example 3 on the TPU film by using a scraper, drying in an oven and laminating with a transparent PET film to obtain the UV-curable insulating tape.

[0094] Example 4

[0095] A UV-curable insulating tape for a cylindrical battery water-cooling plate, which differs from Example 1 only in that the UV-curable acrylic adhesive provided in Preparation Example 4 is used to replace the UV-curable acrylic adhesive provided in Preparation Example 1, and other structures, materials and preparation methods are the same as those in Example 1.

[0096] Example 5

[0097] A UV-curable insulating tape for a cylindrical battery water-cooling plate, which differs from Example 1 only in that the UV-curable acrylic adhesive provided in Preparation Example 5 is used to replace the UV-curable acrylic adhesive provided in Preparation Example 1, and other structures, materials and preparation methods are the same as those in Example 1.

[0098] Example 6

[0099] A UV-curable insulating tape for a cylindrical battery water-cooling plate, which differs from Example 1 in that the thickness of the insulating substrate is 10 μm, and other structures, materials and preparation methods are the same as those in Example 1.

[0100] Example 7

[0101] A UV-curable insulating tape for a cylindrical battery water-cooling plate, which differs from Example 1 in that the thickness of the insulating substrate is 200 μm, and other structures, materials and preparation methods are the same as those in Example 1.

[0102] Comparative Example 1

[0103] An insulating tape for a cylindrical battery water-cooling plate, which differs from Example 1 in that the UV-curable acrylic adhesive provided in Comparative Preparation Example 1 is used to replace the UV-curable acrylic adhesive provided in Preparation Example 1, and other structures, materials and preparation methods are the same as those in Example 1.

[0104] Performance Test:

[0105] The release film of the UV curing insulating tape was removed, and after irradiation with 3000mJ / cm2, 365nm UV light for 2s, it was attached to an aluminum plate of 25mm×100mm at room temperature, and allowed to stand at room temperature for 72h. After obtaining the sample, the following tests were performed;

[0106] (1) Peel strength: Tested according to the method provided in GB / T2792-2016;

[0107] (2) Shear strength: Test according to the method provided in GBT7124;

[0108] (3) Anti-bending effect: Punch out a 90° chamfer of R10 along the center of the long side of the cured sample with the tape on the inside. Leave it for 72 hours to observe whether the tape bounces off.

[0109] (4) Double 85 peel strength: After being placed in an environment of 85℃ / 85% for 1000 hours, the test is carried out according to the method provided in GB / T2792-2016

[0110] (5) Anti-bending effect after double 85: Punch out a 90° chamfer of R10 along the center of the long side of the cured sample with the tape on the inside. Place it in an environment of 85℃ / 85% for 1000 hours and then observe whether the tape bounces off.

[0111] The UV curing insulating tapes provided in Examples 1 to 7 and Comparative Example 1 were tested according to the above test method. The test results are shown in Table 1:

[0112] Table 1

[0113]

[0114] From the data in Table 1, we can see that:

[0115] The peel strength of the UV-curable insulating tapes provided in Examples 1 to 3 is greater than 10 N / 25 mm, and the shear strength is greater than 7 MPa; while the peel strength and shear strength of the insulating tape provided in Comparative Example 1 are both relatively low.

[0116] Compared with Example 1, the proportion of epoxy resin in the raw materials for preparing the UV-curable acrylic pressure-sensitive adhesive in the UV-curable insulating tape provided in Examples 4 to 5 is too high or too low, resulting in low peel strength and shear strength, and poor anti-bending effect.

[0117] Compared with Example 1, the thickness of the insulating substrate in the UV-curing insulating tapes provided in Examples 6 to 7 is too low or too high, which leads to low peel strength, shear strength and poor anti-bending effect.

[0118] The applicant declares that the present invention illustrates a UV-curing insulating tape for a cylindrical battery water-cooling plate and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A UV curing insulating tape for a cylindrical battery water cooling plate, characterized in that: The UV curing insulating tape comprises an insulating substrate, a UV curable acrylic pressure-sensitive adhesive and a release film which are arranged in sequence.

2. The UV curable insulating tape according to claim 1, characterized in that: The thickness of the insulating substrate is 10 to 200 μm, preferably 50 to 100 μm; Preferably, the material of the insulating substrate includes any one of polyethylene terephthalate, polyvinyl chloride, thermoplastic polyolefin, thermoplastic polyurethane elastomer, polyamide, polyethylene or polypropylene, or a combination of at least two thereof.

3. The UV curable insulating tape according to claim 1 or 2, characterized in that: The thickness of the UV-curable acrylic pressure-sensitive adhesive is 20-100 μm.

4. The UV curable insulating tape according to any one of claims 1 to 3, characterized in that: The raw material for preparing the UV-curable acrylic pressure-sensitive adhesive is UV-curable acrylic adhesive solution; Preferably, the UV-curable acrylic adhesive comprises the following components in parts by weight: 10 to 90 parts by weight of acrylate polymer; 10 to 90 parts by weight of epoxy resin; 0.5 to 5 parts by weight of photoinitiator; Preferably, the acrylate polymer is formed by free radical polymerization of structural monomers and optionally functional monomers; Preferably, the structural monomer includes any one or a combination of at least two of methyl acrylate, methyl methacrylate, butyl acrylate, isooctyl acrylate, isobornyl acrylate or isobornyl methacrylate; Preferably, the functional monomer comprises a combination of at least two of acrylic acid, methacrylic acid, glycidyl methacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, acrylamide, N-vinyl caprolactam or N-vinyl pyrrolidone; Preferably, the epoxy resin includes any one of bisphenol A epoxy resin, hydrogenated bisphenol A epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol F epoxy resin, bisphenol S epoxy resin, hydrogenated bisphenol S epoxy resin, novolac epoxy resin, hydrogenated novolac epoxy resin, biphenyl epoxy resin, hydrogenated biphenyl epoxy resin, phenol epoxy resin, hydrogenated phenol epoxy resin, distyrene epoxy resin, polyurethane modified epoxy resin, polyether modified epoxy resin, rubber modified epoxy resin, silicone modified epoxy resin, dimer acid modified epoxy resin or aliphatic epoxy resin, or a combination of at least two thereof; Preferably, the photoinitiator comprises any one or a combination of at least two of a diazonium salt, a diaryliodonium salt, a triarylsulfonium salt, an alkylsulfonium salt, an iron arene salt or a sulfonyloxy ketone; Preferably, the UV-curable acrylic adhesive further comprises any one or a combination of at least two of a tackifying resin, a flame retardant or a filler; Preferably, the content of the tackifying resin in the UV-curable acrylic adhesive is ≤10 parts by weight; Preferably, the tackifying resin comprises any one of aromatic resin, rosin terpene phenol resin or modified rosin resin or a combination of at least two thereof; Preferably, the content of flame retardant in the UV-curable acrylic adhesive is ≤30 parts by weight; Preferably, the flame retardant includes any one or a combination of at least two of a phosphorus flame retardant, a nitrogen flame retardant, a silicon flame retardant, a metal hydroxide flame retardant, a metal oxide flame retardant, a flame retardant acrylic resin or a metal boride flame retardant; Preferably, the content of filler in the UV-curable acrylic adhesive is ≤5 parts by weight; Preferably, the filler comprises fumed silica; Preferably, the fumed silica includes any one of AEROSIL 150, AEROSIL 200 or AEROSIL 380, or a combination of at least two of them.

5. The UV curable insulating tape according to any one of claims 1 to 4, characterized in that: The thickness of the release film is 25 to 100 μm, preferably 25 to 50 μm; Preferably, the release film comprises a transparent PET release film.

6. A method for preparing the UV curable insulating tape according to any one of claims 1 to 5, characterized in that: The preparation method comprises: coating a UV-curable acrylic adhesive on an insulating substrate, and laminating a release film after drying to obtain the UV-curable insulating tape.

7. A method for using the UV curing insulating tape according to any one of claims 1 to 5, characterized in that: The method of use comprises: sticking the UV curing insulating tape on the surface of the cylindrical battery water cooling plate, and performing UV curing and standing to complete the use of the UV curing insulating tape.

8. The method of use according to claim 7, characterized in that: The energy density of the UV curing is 1000-5000 mJ / cm 2 ; Preferably, the UV curing time is 1 second to 5 hours.

9. The method of use according to claim 7 or 8, characterized in that: The static temperature is room temperature; Preferably, the standing time is 1 to 100 hours.

10. Use of the UV curable insulating tape according to any one of claims 1 to 5 in the preparation of cylindrical batteries for vehicles.